Pararoseburia lenta gen. nov., sp. nov. isolated from human faeces. Issue 5 (13th May 2022) - Abdugheni, Rashidin; Wang, Yu-Jing; Li, Dan-Hua; Du, Meng-Xuan; Liu, Chang; Zhou, Nan; Liu, Shuang-Jiang
Abstract : A strictly anaerobic, motile bacterium, designated as strain NSJ-9 T, was isolated from human faeces. Cells were Gram-negative, non-spore-forming, non-pigmented, and spiral-shaped or slightly curved rods with flagella. Optimal growth in M2GSC medium was observed at 37 °C (growth range 30–45 °C) and pH 6.5–7.0 (growth range 6.5–7.5) under anaerobic conditions. Phylogenetic analysis of the 16S rRNA gene revealed that strain NSJ-9 T formed a distinct phylogenetic lineage that reflects a new genus in the family Lachnospiraceae, with high levels of similarity to Roseburia hominis A2-183 T (95.2 %), Roseburia cecicola ATCC 33874 T (95.2 %), Pseudobutyrivibrio ruminis DSM 9787 T (95.2 %), Pseudobutyrivibrio xylanivorans MZ 5 T (94.8%) and Roseburia faecis M72/1 T (94.4 %). Genomic similarity (average nucleotide identity and digital DNA–DNA hybridization) values between strain NSJ-9 T and its phylogenetic neighbours were below 71 and 31 %, respectively, indicating that strain NSJ-9 T represented a novel species. The average amino acid identity and the percentage of conserved proteins between strain NSJ-9 T and other related members of the family Lachnospiraceae were below 63 and 50 %, respectively, supporting that strain NSJ-9 T was a member of a new genus. The predominant cellular fatty acids of strain NSJ-9 T were C16 : 0 and C17 : 0 2-OH, and major polar lipids were glycolipids. The end products of glucose fermentation were acetate, propionate, iso-butyrate, butyrate and valerate. Phylogenetic and phylogenomic lineage, pairwise determined genome identity analysis suggested that strain NSJ-9 T represents a novel genus in the family Lachnospiraceae . The genome size of strain NSJ-9 T is 2.56 Mbp with 44.9 mol% G+C content. Collectively, the genotypic and phenotypic differences between phylogenetic relatives suggested strain NSJ-9 T represented a novel species of a new genus, for which the name Pararoseburia lenta gen. nov., sp. nov. is proposed. The type strain of Pararoseburia lenta is NSJ-9 T (=CGMCC 1.32469 T =KCTC 15957 T ).